A Study on Age at Menarche with its Relation To Pregnancy Induced Hypertension - Lahiri, Arista; Bandyopadhyay, Soumyajyoti; Adhya, Shouvanik; Ghosh, Somanjana; Ray, Sumita; Haldar , Swaraj (Journal of Indian Academy of Forensic Medicine, 2015)
It is a well-established fact that the age at which a girl should attain menarche is dependent not  only on hormonal factors of that particular female but a number of genetic, nutritional as well as  environmental factors play significant role in the age of onset of the event. Often in our clinical set-up, we  observe the similar age of onset of menstruation among girls of the same family. Now in this cross sectional observational study with a study population of 260 pregnant women of varying age groups, we  try to make an attempt to establish a relationship between the age at Menarche of this randomly selected  study population with incidence of Pregnancy Induced Hypertension in the same population, though it is a  well-known fact that all the three entity pregnancy induced hypertension, preeclampsia & eclampsia have  a multi factorial etiology. It has been found out from the present study that there is a statistically  significant association between menarche at an early age with occurrence of pregnancy induced  hypertension especially in cases of the primigravida.
Keywords: Hypertension; Menarche; Multigravida; Pregnancy; Primigravida